CASK, the Soluble Glomerular Permeability Factor, Is Secreted by Macrophages in Patients With Recurrent Focal and Segmental Glomerulo—Sclerosis - Zhang, Xiaomeng; Herr, Florence; Vernochet, Amelia; Lorenzo, Hans K.; Beaudreuil, Séverine; Dürrbach, Antoine (Frontiers in Immunology, 2020)
Introduction: Focal and segmental glomerulosclerosis (FSGS) is a frequent form of glomerulonephritis that may be caused by a soluble permeability factor and regulated by the immune system. We previously described a soluble form of calcium/calmodulin-dependent serine/threonine kinase (CASK) acting as a permeability factor in patients with recurrent FSGS (rFSGS). Here, we aimed to identify the immune cells associated with CASK secretion in patients with rFSGS. Methods: FACS, western blotting and immunoprecipitation were performed to detect CASK in peripheral blood mononuclear cells, including CD3+, CD20+, and CD14+subsets, from patients with rFSGS, healthy donors, transplant patients and patients with nephrotic syndrome due to diabetes mellitus, and in KHM2 cells. Results: CASK was produced mostly by monocytes in patients with rFSGS but not by T or B lymphocytes. It was not detectein cells from control patients. CASK was also produced and secreted by M2 polarized macrophages and KMH2 cells, but not by M1 polarized macrophages. CASK secretion was not not inhibited by brefeldin A, suggesting an absence of classical secretion pathway involvement. Within cells, CASK was partly colocalized with ALIX, a molecule involved in exosome development, and these two molecules were coprecipitated from M2 macrophages. Moreover, exosomes derived from M2 macrophages induced podocyte cytoskeleton alterations and increased podocyte motility. Conclusion: These results suggest that the soluble permeability factor CASK is secreted by monocytes and M2 macrophages, via exosomes, to alter the glomerular filtration barrier in rFSGS.